Kajian Regiokimia Markovnikov Melalui Mekanisme Reaksi Hidrasi Alkuna Terminal pada Etinilestradiol dengan Katalis FeCl3 - Hotma Rotua Br. Simbolon; Rymond Jusuf Rumampuk; Anderson Arnold Aloanis (Jurnal Kimia Fullerene, 2021)
The terminal alkynes hydration reaction on 17Î±-ethynylestradiol (1) with FeCl3 catalyst mediated by dichloromethane aims to determine the reaction products produced and to conduct a Markovnikov regiochemistry study through the proposed reaction mechanism. The reaction conditions were carried out at a temperature of 50oC (48 hours) and 60oC (19 hours), the separation of the reaction properties was carried out using Gravity Column Chromatography, and the reaction products were identification using by Proton Nuclear Magnetic Resonance (1H-NMR). Here we describe the process of the FeCl3 catalyst forming a coordination complex with the terminal alkyne, which is then addition by nucleophilic water following Markovnikov's regiochemistry to finally produce the product of a methyl ketone, 17Î±-acetylestradiol (6). The catalyst used is a cationic ligand coordinate, where Fe3+ is a Lewis acid and Cl3- acts as a ligand. The dichloromethane solvent used can also increase the reaction rate.